The Output Consensus Problem of DC Microgrids With Dynamic Event-Triggered Control Scheme - Geng, Yan; Ji, Jianwei; Hu, Bo (Frontiers in Energy Research, 2021)
In this paper, the output consensus problem of DC microgrids with dynamic event-triggered control scheme is investigated. According to the properties of DC microgrids and multi-agent systems, the multi-agent systems function model for DC microgrids is provided. For making the multi-agent systems achieve output consensus, the non-periodic and periodic dynamic event-triggered control schemes are provided, respectively, which are classified according to the style of receiving information. By using a series of analysis, it can be proved that these two control schemes not only can make systems achieve output consensus, but also can avoid the Zeno-behavior successfully. Moreover, the periodic dynamic event-triggered control scheme does not need the continuous information transfer. Finally, a numerical example is provided to support our conclusions.